2021
DOI: 10.1136/bmjopen-2021-049274
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of a rural-oriented physician education programme against rural physician shortages in Guangxi province: a prospective cohort study

Abstract: ObjectivesThis study aimed to investigate early outcomes of one of the first medical undergraduate education programmes with a goal of mitigating severe rural physician shortages in China, which was developed by Guangxi Medical University (GXMU) and was called the Rural-oriented Free Tuition Medical Education (RTME)-GXMU programme.DesignA prospective cohort study comprising a baseline investigation and follow-up research was conducted to dynamically observe the evolution of the RTME-GXMU programme that began s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Semi-structured interviews with all 45 students found that the low success rate promoting General Practice was attributed to: the relatively low salary and poor working conditions of GPs (41, 91%); low social status; concerns about career prospects(45, 100%); not able to focus on medical work because of multiple roles including preventive medicine, public education etc. (42, 93%); the living conditions at the working locations are not desirable (43, 95%) 2010 Rural-on-Demand-Oriented-bonded-GP Training Programme [ 21 , 53 , 55 – 58 , 60 ] Students enrolled in this five-years programme are predominantly recruited from rural areas, and priority is given to those from areas designated most in need of health care. Students are exempt from tuition and accommodation fees and central government provides 6,000 Yuan (approximately USD913) per year for living expenses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Semi-structured interviews with all 45 students found that the low success rate promoting General Practice was attributed to: the relatively low salary and poor working conditions of GPs (41, 91%); low social status; concerns about career prospects(45, 100%); not able to focus on medical work because of multiple roles including preventive medicine, public education etc. (42, 93%); the living conditions at the working locations are not desirable (43, 95%) 2010 Rural-on-Demand-Oriented-bonded-GP Training Programme [ 21 , 53 , 55 – 58 , 60 ] Students enrolled in this five-years programme are predominantly recruited from rural areas, and priority is given to those from areas designated most in need of health care. Students are exempt from tuition and accommodation fees and central government provides 6,000 Yuan (approximately USD913) per year for living expenses.…”
Section: Resultsmentioning
confidence: 99%
“…Students are exempt from tuition and accommodation fees and central government provides 6,000 Yuan (approximately USD913) per year for living expenses. On course completion graduates are obligated to serve in a rural primary medical and health institutions for a minimum of 6 years or pay a penalty Six studies [ 21 , 53 , 56 – 58 , 60 ] [ 55 ] from Guangxi, Zhejiang, Yunnan, Anhui and one unspecified locations report on the outcome of this programme. Three studies [ 21 , 56 , 57 ] reported that the majority of the students were willing to or did become GPs after graduation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty two provinces that suffered severe rural physician shortage in central and western China were targeted. Students with rural backgrounds were exclusively recruited and were subsidized to complete the 5-years undergraduate studies [ 12 ]. In return, students are obligated to provide rural health service as general practitioners (GPs) in designated THCs for 6 years, during which 3 years were required for the standardised residency training (SRT) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%